Mercy and failed marriages: some considerations facing a possible juridical and pastoral rethink - Callejo de Paz, Rufino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Having the Jubilee of Mercy as a main reference, and facing the challenges posed by the Synod on the Family, this paper attempts to present the canonical solutions in case of failed marriages and the possible new ways that can be considered from the point of view of canon law. Regarding the marriage nullity cases, I expound the deficiencies I perceive in the current praxis, and regarding canonical dissolutions, the possibility of delving into the full meaning of sacramentality and consummation. From this, I propose to extend the canonical solutions in favor of the faith and the salus animarum.